Pembuatan sistem informasi inventarisasi tanaman berbasis QR code untuk identifikasi tanaman Taman Hutan Kota HM Sabki Kota Jambi - Ulfa Khaira; Tri Suratno; Mauladi Mauladi; Reni Aryani; Edi Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The Urban Forest of HM Sabki has great potential as a tourist destination, not only as a recreation area but also as a center for research and plant conservation. For this reason, the Urban Forest of HM Sabki is expected to be able to provide adequate information about its plants. This community service program creates a plant inventory information system and QR code as a marker of plants that can be scanned using a smartphone. This technology enables visitors to access detailed information about plants. QR code is a printed 2-dimensional image code that can store data. This technology can display information about plants that have been previously entered by the manager into the plant inventory information system. Through this application, the Urban Forest management can easily manage all information about plants.